THE EFFECT OF THE "HY-BON HYDROCARBON" EDUGAME MEDIA ON HYDROCARBON DERIVATIVE MATERIALS ON THE LEARNING OUTCOMES OF STUDENTS IN CLASS 12 MIPA 7 SMA NEGERI 3 SIDOARJO - Deni Ainur Rokhim; Dede Yayah Rokayah; Sabhrina Nabilah; Fathin Salsabila Alfarisi (Jurnal Pembelajaran Sains, 2021)
This study aims to determine the effect of edugame media "hy-bon hydrocarbons" on hydrocarbon derivatives on the learning outcomes of students in grade 12 MIPA 7 SMA Negeri 3 Sidoarjo. Quantitative data collection with 20 students as a sample who answered the pretest and posttest questions. The results showed that the "hy-bon hydrocarbon" educational media on hydrocarbon derivative materials had an effect on student learning outcomes. This is evidenced by the results of data processing using the normality test and t-test which shows the influence of the "hy-bon hydrocarbon" edugame media on student learning outcomes. And indicated by the value of the t count is greater than the t table. That is 8.608 > 2.037 . So Ho is rejected and Ha is accepted.